(untitled) (Confluenţe Bibliologice, 2025)
The author tells about the Castle of Ruginoasa , that is actually a museum and belongs to the Moldova National Museum Complex in Iasi. Ruginoasa estate belonged to Sturdza Sandulache, the schancellor, who built a palace, a park and a stone church.Rebuilt in neo-Gothic style the castle from Ruginoasa was among the few buildings of this size and preciousness in Moldova.The history and events of this castle are described in the book ,"Ruginoasa " written by Theodor Răşcanu, published by the Publishing House "Weather" in October 1938.